EXTRACTION OF GAHARU OIL FROM AQUILARIA MALACCENCIS USING SUBCRITICAL EXTRACTION PROCESS - Mohd Radzi, H.C.D.; Huzaifah, Hamdan (2016)
Aquilaria species from the family of Thymelaeceae are the main source of gaharu, which has been classified as one of the most highly valuable, non-timber products in the world market. Currently, the method used for extracting gaharu essential oil is by using hydrodistillation. However, this method is inefficient where it produced low yield of oil with long time of extraction and thus increasing the production cost. To overcome this problem, the extraction of gaharu essential oil using Supercritical Fluid Extraction (SFE) with pressure 20MPa, 30MPa and 40MPa at 65 °C for 2 hours was studied. Result obtained after 2 hours of experiment was 0.6% of yield, which was higher compared to 0.2% yield of gaharu essential oil obtained via 3 days of hydrodistillation. After an extraction process, the product will be analyzed by using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the chemical compounds and composition in the Gaharu SFE’s extract. Over eighteen to thirty-one compounds were identified in SFE extract compared with fifty-five identified in the hydrodistillated oil. The mutual occurrence of chemical compounds in all three samples in SFE was dimethyl phthalate, 8-epi-.gama.-eudesmol, diethyl Phthalate and 2-3-Butanediol. In comparison, the major compounds identified in hydrodistillated oil were 4-phenyl-2-butanone, jinkoh-eremol and α-guaiene (Saiful Nizam & Mashitah, 2010). There were certain aromatic sesquiterpenes compounds that were identified in this study, such as Globulol, Alloaromadendrene Naphthalene, 10s, 11s-Himachala-3(12), 4-diene, .delta.-Selinene and (-) - Aristolene.